MICRO AND SMALL ENTERPRISES PERFORMANCE EVALUATION SYSTEM - Rakhma Oktavina, M. Syamsul Ma’arif, Eriyatno dan Erliza Hambali (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT The performance could be managed effectively and efficiently if it was supported by an optimal performance evaluation process, consisting of measurement and improvement model. In this study, the performance evaluation system was developed through strategic management approach, where expert knowledge is acquired by an in depth interview methods. The aim of this research is to develop a model of performance evaluation to micro and small enterprises. The performance evaluation system composed by 3 sub systems, i.e. (1) data based management system, (2) model based management system, and (3) knowledge based management system. Evaluation process consists of four stages, i.e. key performance indicators and technical responses identification process, measurement performance process, improvement performance and  recommendation determination process, and implementation process.  Verification and validation process shows that the model of performance evaluation process has been able to represent the banana chip’s micro and small enterprises performance evaluation system at Lampung province.     Keywords : Micro and small enterprises,  evaluation performance system, strategic management